Psychiatric hospital utilisation following lithium discontinuation in patients with bipolar I or II disorder: A mirror-image study based on the lisie retrospective cohort. (13th April 2021) - Öhlund, L.; Ott, M.; Bergqvist, M.; Oja, S.; Lundqvist, R.; Sandlund, M.; Renberg, E. Salander; Werneke, U.
Abstract : Introduction: Evidence for lithium as a maintenance treatment for bipolar disorder type II remains limited since most treatment-prevention studies focus on bipolar disorder type I or do not distinguish between types of bipolar disorder. Objectives: To compare the impact of lithium discontinuation on hospital utilisation in patients with bipolar disorder type I or schizoaffective disorder and patients with bipolar disorder type II or other bipolar disorder. Methods: Mirror-image study, examining hospital utilisation within two years before and after lithium discontinuation as part of LiSIE, a retrospective cohort study into effects and side-effects of lithium for the maintenance treatment of bipolar disorder as compared to other mood stabilisers. Results: For the whole sample, the number of admissions increased from 86 to 185 admissions after lithium discontinuation, with the mean number of admissions/patient/review period doubling from 0.44 to 0.95 (p < 0.001). The number of bed days increased from 2218 to 4240, with the mean number of bed days/patient/review period doubling from 11 to 22 (p = 0.025). This increase in admissions and bed days was exclusively attributable to patients with bipolar disorder type I or schizoaffective disorder. Conclusions: Our findings suggest that due to a higher relapse risk in patients with bipolar disorder type I or schizoaffective disorder there is a need to apply a higher threshold for discontinuing lithium than for patients with bipolar disorder type II or other bipolar disorder. Disclosure: Michael Ott has been a scientific advisory board member of Astra Zeneca Sweden, Ursula Werneke has received funding for educational activities on behalf of Norrbotten Region (Masterclass Psychiatry Programme 2014–2018 and EAPM 2016, Luleå, Sweden): Astra